Comparison of PCR and Loop Mediated Isothermal Amplification Method for Detection of Salmonella spp. in Chicken Meat - Pargi, Zalak B; Nayak, Jeetendra B; Brahmbhatt, Manoj N; Bhong, Chandrakant D; Macwan, Terrance; Thakur, Sonali (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The aim of the study was to compare Polymerase Chain Reaction (PCR) and Loop Mediated Isothermal Amplification (LAMP) assay for detection of Salmonella in Chicken Meat. Food safety remains a major concern worldwide, with outbreaks of foodborne illness resulting in significant costs to individuals and to the food industry. The Salmonella genus is the most prevalent group of foodborne pathogens that are regularly isolated from food-producing animals and thus are one of the leading causes of food borne diseases. Out of total 40 Salmonella isolates, LAMP and PCR assay detected 36 (90%) and 32 (80%) isolates, respectively. The sensitivity of the LAMP assay was noted to be 10-fold higher than that of PCR whereas the specificity of both LAMP and PCR was same.